Multi-event contingency analysis for voltage stability study / Norarian Minhat - Minhat, Norarian (2007)
Contingency analysis is one of the important components in voltage stability studies. This is due to the fact that, contingency can cause a system to experience voltage instability condition. One of the possible events is that, when a line is on outage, the corresponding load bus will experience a stress condition leading to overall system instability. Prior to the contingency analysis, system constraints will be first identified. Consequently contingency analysis will be performed which could be caused by line or generator outage or load curtailment. Voltage stability studies will be then conducted to the system with all these scenarios.